Retrieving And (Re-reading) My Teenage On-Line Diaries: A Feminist Study Of A Young Girl's Passage Into Identity Construction - Meksawat , Mattanyu (2016)
“Archive is the complex and incomplete site of women’s knowledge” (Carr, 2001: 1). Joining the MA program in Women, Gender and Sexuality Studies in mid-2015 and having taken courses related to the issues of women, history and archives haves brought me to a (very familiar but) forgotten chapter of my life; that is, the digitalized diary of my teenage (and younger woman) years (2005-2009). In this study the 103 entries of my online diary published on “yenta4.com” (which has recently been closed) will be retrieved and elaborated upon through the framework and practice of “autoethnography” as discussed by Ellis (2000), Dent (2002) and others. It will reflect the passage of a rural teenager in various ways such as struggling to adjust her life in a very large and complex capital city, dealing with the hardship of study at the high school level and above all learning about one's sexuality through relationships with loving friends of the opposite gender. As the issues of “Girl Studies” by the girl’s (own) voice from a feminist perspective is rarely touched upon in the academic circles of Women’s Studies in Thailand, this research aims to open up, contribute and strengthen the body of knowledge in this area.